Desire for parenthood at the time of COVID-19 pandemic: an insight into the Italian situation - Elisabetta Micelli; Gianmartin Cito; Andrea Cocci; Gaia Polloni; Giorgio Ivan Russo; Andrea Minervini; Marco Carini; Alessandro Natali; Maria Elisabetta Coccia (Taylor & Francis Group, 2020)
Purpose: To evaluate the impact of the COVID-19 pandemic lifestyle change on couples of reproductive age and on their desire for parenthood. Materials and methods: A quantitative correlational research study, based on a web survey, was conducted among Italian men and women in heterosexual stable relationships, aged between 18 and 46 years. The self-administered Italian version questionnaire was created using Google Forms and posted on chats and social networks.The mood of participants before and during the quarantine was assessed using a scale from 1 to 10 (1 = no wellbeing; 10 = total wellbeing). Couples' quality of life and their reproductive desire were evaluated. Results: 1482 respondents were included: 944 women (63.7%) and 538 men (36.3%). A significant trend toward reduced mean wellbeing scores during the quarantine, compared to before, was found (p < .01). From 18.1% participants who were planning to have a child before the pandemic, 37.3% abandoned the intention, related to worries of future economic difficulties (58%) and consequences on pregnancy (58%). Of 81.9% who did not intend to conceive, 11.5% revealed a desire for parenthood during quarantine than before (p < .01), related to will for change (50%) and need for positivity (40%). 4.3% of these actually tried to get pregnant. Stratifying by age, a trend toward older ages was found in the desire for parenthood before and during the COVID-19 pandemic (p < .05). Conclusions: COVID-19 pandemic is impacting on the desire for parenthood. It is unknown whether these findings will result in a substantial modification of birth rate in the near future.